AN IMPORTANCE PERFORMANCE ANALYSIS ON ‘KERIPIK BELEDANG’ BENGKULU ATRIBUTES AS SATISFACTION QUALITY MEASURE IN FOOD INDUSTRY - Zulman Efendi; Evanila Silvia; Reko Rahmad Wijaya (BPFP Faperta UNIB, 2018)
Costumer satisfaction is comparison beetwen costumer’s expected satisfaction and actual performance. The aims of research were to identify the Beledang Chips attributes that consumers need, improvement factor (IF), determine the costumer satisfaction index (CSI) and get a map attributes of beledang chips. The research was conducted by purpossive sampling. The result showed there were 13 attributes considered by consumers for their interest in Beledang Chips. The highest score of IF was color, CSI level was 0.93 that classified as highly satisfied. Based on attributes mapping, average satisfaction and importance performance were 3.93 and 4.30. There was the color product in quadrant A for top priority, then packaging practices, packaging capabilities, oily impression, price suitability, without preservatives in quadrant B for keep up the good work, then lay out and attractive illustration, variant packaging, packaging colors, special pricing, cruncy, uniformity of size in quadrant C for low priority, and discount in quadrant D for not expected. Thus, the business development of Beledang Chips Bengkulu can follow the advice as the awareness of the research results.